Genome wide association mapping through 90K SNP array against leaf rust pathogen in bread wheat genotypes under field conditions - Hafiz Ghulam Muhu-Din Ahmed (Elsevier, 2021)
In wheat crop the leaf rust is an infectious disease, threatening wheat production annually. Identification of resistance genes or markers traits associations for effective field resistance could greatly enhance our ability to breed durably resistant varieties. Herein 105 bread wheat genotypes were evaluated against the leaf rust susceptible and resistance during the two seasons 2018–19 and 2019–20 under field conditions using CI, AUDPC and FDS parameters. Based on the performance of genotypes against leaf rust pathogen, 34 genotypes categorised as resistance (R), followed by 30, 32 and 9 genotypes classified as moderately resistance (MR), moderately susceptible (MS) and susceptible (S) genotypes. respectively. We also applied a genome wide association study (GWAS) approach to identify markers trait associations (MTAs) resistance against leaf rust using 90 K SNP Array. Marker–trait association results indicated that total 56 MTAs were significantly associated at P ≤ 10−3 using Bonferroni adjustment after crossed FDR ≤ 0.05 with studied parameters under field conditions. Among them, total numbers of associated MTAs 17, 23 and 16 were identified for CI, AUDPC and FDS parameters, respectively. Maximum significant MTAs were identified on chromosomes 2A (7), 3B (7), 5A (7) followed by 4A (5), 7B (5), 1A (4) and 7A (4) in the studied genotypes. The locus (Kukri_c55051_414) showed pleotropic effects for leaf rust identified parameters on chromosome 5A at position of 68.2 cM under field conditions. This study demonstrated the use of genome-wide association mapping for the identification of potentially new genomic regions associated with studied parameters. Leaf rust resistant genotypes identified in this study proved to be more productive under preliminary field conditions against leaf rust pathogen. Thus, these resistant accessions could be used as parental genotypes in breeding programs for leaf rust resistance.